Genetics of eukaryotic RNA polymerases I, II, and III. - Archambault, J (1993)
The transcription of nucleus-encoded genes in eukaryotes is performed by three distinct RNA polymerases termed I, II, and III, each of which is a complex enzyme composed of more than 10 subunits. The isolation of genes encoding subunits of eukaryotic RNA polymerases from a wide spectrum of organisms has confirmed previous biochemical and immunological data indicating that all three enzymes are closely related in structures that have been conserved in evolution. Each RNA polymerase is an enzyme complex composed of two large subunits that are homologous to the two largest subunits of prokaryotic RNA polymerases and are associated with smaller polypeptides, some of which are common to two or to all three eukaryotic enzymes. This remarkable conservation of structure most probably underlies a conservation of function and emphasizes the likelihood that information gained from the study of RNA polymerases from one organism will be applicable to others. The recent isolation of many mutations affecting the structure and/or function of eukaryotic and prokaryotic RNA polymerases now makes it feasible to begin integrating genetic and biochemical information from various species in order to develop a picture of these enzymes. The picture of eukaryotic RNA polymerases depicted in this article emphasizes the role(s) of different polypeptide regions in interaction with other subunits, cofactors, substrates, inhibitors, or accessory transcription factors, as well as the requirement for these interactions in transcription initiation, elongation, pausing, termination, and/or enzyme assembly. Most mutations described here have been isolated in eukaryotic organisms that have well-developed experimental genetic systems as well as amenable biochemistry, such as Saccharomyces cerevisiae, Drosophila melanogaster, and Caenorhabditis elegans. When relevant, mutations affecting regions of Escherichia coli RNA polymerase that are conserved among eukaryotes and prokaryotes are also presented. In addition to providing information about the structure and function of eukaryotic RNA polymerases, the study of mutations and of the pleiotropic phenotypes they imposed has underscored the central role played by these enzymes in many fundamental processes such as development and cellular differentiation.